LOW COST FRESHWATER FISH PICKLE USING CHEAP CITRUS FRUIT (C.RETICULATA) - CHATTOPADHYAY, A k; BANDYOPADHYAY, J k; BHATTACHARYYA, S k (Fishery Technology, 2017)
The juice extracted from a locally abundant cheap variety of citrus fruit namely, Citrus reticulata was utilized for pickling. The paper highlights the trials made to select the optimum concentrations of acetic acid and sodium chloride to be used along with the juice of C. reticulata so as to obtain the best, product. The product can be stored well at room temperature for six months.